Minimally Invasive Laminate Veneers: Clinical Aspects in Treatment Planning and Cementation Procedures - R. K. Morita; M. F. Hayashida; Y. M. Pupo; G. Berger; R. D. Reggiani; E. A. G. Betiol (Hindawi Limited, 2016)
When a definitive aesthetic treatment is determined, it is crucial to grant the patient's wish with the necessary dental treatment. Thus, conservative treatments that are the solution to aesthetic problems involving morphologic modifications and provide the result that the patient expects should always be the first therapeutic option. In this context, ceramic laminate veneers, also known as "contact lens," are capable of providing an extremely faithful reproduction of the natural teeth with great color stability and periodontal biocompatibility. Minimal or no preparation veneers are heavily advertised as the answer to our patients' cosmetic needs, which they can be if they are used correctly in the appropriate case. This report is about ultraconservative restorations to achieve functional and aesthetic rehabilitation through treatment planning. Thus, clinicians should be aware that the preparation for laminate veneers remains within enamel, to ensure the bond strength and avoid or minimize the occurrence of postoperative sensitivity.